Effect of Junction Geometry on Monodispersed Microdroplet Generation in Microfluidic Aqueous Two-Phase Systems - (:unkn) unknown (My University, 2014)
Aqueous two-phase system (ATPS) consists of two immiscible water-based solutions of polymers, which can form phase partitioning. Dextran and polyethylene glycol I used in this thesis is the one of common components of aqueous two-phase system give a reliable and incompatible environment for purification of biomedical products and cellular macromolecules. Recently, ATPS have received increasing attention as a separation method in microfluidic device due to the advantages of biocompatibility, unlimited combination, and low interfacial tension. Hence, it became an important to discover researches related to ATPS microfluidic device. Microdroplets produced in microfluidic device are a largely interesting phenomenon for various applications. Monodisperse and size manageable microdroplets using ATPS could potentially be used to better micro-enviornment. However, extremely low interfacial tension (≤ 100 μN/m) leading to viscoelastic fluid (non-Newtonian) characteristic makes it difficult to generate microdroplets. It is necessary to control the physical and topological behavior of ATPS. Therefore, this thesis aims to study fluid mechanism for droplet-based microfluidics using ATPS. Droplet generation using aqueous two phase systems (ATPS) in microfluidic device was studied by various junction areas which were considered as T-junction, flow-focusing, and double-flow-focusing. The characteristic of low interfacial tension and high viscosity between aqueous phases was the challenge to produce uniform micro-droplets. The importance of this experiment is that in contrast to another external installations previously studied, double-flow-focusing channel drew advantages of simple method, cost effective, and heavy workload. Without the continuous mechanical pressure by pressure-driven flow, no external actuations were used. T-junctions and flow-focusing, broadly used for microfluidic device, were compared with double-flow-focusing channel. The role of each flow-focusing junction for monodisperse water-in-water (w/w) droplets was investigated. Additional flow-focusing junction for monodisperse water-in-water (w/w) droplets brought the consequence different from T-juntion and flow-focusing. Moreover, I proved that PEG and Dextran droplets within double-flow-focusing could be formed with combination of two continuous flow rates. Surfactant impact on droplet generation in ATPS was studied. Thus, a double-flow-focusing microfluidic device I developed was able to be a crucial method to generate water-in-water (w/w) droplets due to the stability of dispersion between two junction areas.
Keywords: Aqueous Two-phase System; Dextran Polyethylene Glycol; Droplet; Microfluidic Aqueous Two-phase System; Microfluidics; Monodispersity